SCIENCE PERSPECTIVE: A STUDY OF CALORIES IN BROWN RICE FRIED RICE - Tinara, Dinda Tia; Sartika, Septi Budi (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to analyze and compare the calorie content of fried rice made from white rice and brown rice, focusing on their nutritional value and potential health benefits. The research highlights the advantages of brown rice as a healthier alternative for fried rice, promoting better calorie control and supporting dietary programs. Method: The study employs a literature review complemented by laboratory-based calorie calculations. Data was collected from previous scientific publications and experimental analyses, including the evaluation of macronutrient compositions and calorie content in both white rice and brown rice variants of fried rice. Results: Laboratory findings reveal that fried rice made from brown rice contains 115.32 kcal per 150 grams, slightly lower than the 115.56 kcal found in fried rice made from white rice. Although the calorie difference is marginal, brown rice fried rice demonstrates superior nutritional benefits, such as higher complex carbohydrate content and a lower glycemic index, which support prolonged satiety and better energy regulation. Novelty: This research introduces a unique perspective on the nutritional profile of fried rice by incorporating brown rice as a primary ingredient. Unlike traditional fried rice studies, this paper emphasizes the use of brown rice to create a low-calorie and nutritionally rich variant, aligning with modern dietary needs and contributing to innovations in Indonesian culinary practices.